2020
DOI: 10.1186/s12906-020-03000-8
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the sedative-hypnotic effect of the extracts of herb pair Semen Ziziphi spinosae and Radix Polygalae and related mechanisms through experiments and metabolomics approach

Abstract: Background: Semen Ziziphi spinosae and Radix Polygalae, two herbs commonly used together in Traditional Chinese Medicine for the treatment of insomnia and anxiety. The study aims to study the sedative-hypnotic effect of the active components of the herbal pair, the possible mechanisms of such effect, and related metabolic pathways in vivo. Methods: The sedative and hypnotic effect of the active components (EI30) of the herbal pair was studied by recording influence on the proportion of sleeping within 30 min, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 28 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…11 Modern pharmacological studies showed that the extracts of Polygalae Radix could prevent glutamate, Aβ and corticosteroneinduced cell injury, improve dysfunction of learning and memory in multiple AD animal models, mediate depression and exert sedativehypnotic effect. [12][13][14][15][16] 3,6'-disinapoyl sucrose (DISS) is a kind of oligosaccharide ester derived from Radix Polygala, which has been used as one of the quality control indices of Polygalae Radix in the Chinese Pharmacopoeia (2015 edition). 11 DISS has antioxidative effects, neuroprotection and anti-depression in cells and animal model.…”
mentioning
confidence: 99%
“…11 Modern pharmacological studies showed that the extracts of Polygalae Radix could prevent glutamate, Aβ and corticosteroneinduced cell injury, improve dysfunction of learning and memory in multiple AD animal models, mediate depression and exert sedativehypnotic effect. [12][13][14][15][16] 3,6'-disinapoyl sucrose (DISS) is a kind of oligosaccharide ester derived from Radix Polygala, which has been used as one of the quality control indices of Polygalae Radix in the Chinese Pharmacopoeia (2015 edition). 11 DISS has antioxidative effects, neuroprotection and anti-depression in cells and animal model.…”
mentioning
confidence: 99%
“…Phenylalanine, via phenylalanine hydroxylase, produces tyrosine, which produces the neurotransmitter dopamine [ 69 ]. The ethanol eluent of Semen ziziphi and Radix polygalae down-regulated phenylalanine, mainly due to the sedative-hypnotic role of the flavonoid and saponin contents [ 70 ]. Glycosides of C. pilosula act as a sedative agent [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…They expounded the action ways of Chinese medicine in regulating central neurotransmitter affecting sleep-related cytokines, and improving the structure of the central nervous system. [ 18 , 19 ]…”
Section: Discussionmentioning
confidence: 99%